Pengaruh Penerapan APD (Alat Pelindung Diri) terhadap Angka Kecelakaan - Puriadi Puriadi; Polina Lase; Ernestia Meilia Br. Sembiring; Daud Arifin (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Personal Protective Equipment (PPE) is a tool that has the ability to protect a person at work whose function is to isolate the body of the workforce from hazards in the workplace. PPE is a personal protective equipment used by the workforce directly to prevent accidents caused by various factors that exist or arise in the work environment. The problem raised is the Effect of the Application of PPE (Personal Protective Equipment) on the Number of Accidents. In this study, the design used is Literature Review. The method in searching article data sources is carried out through the Google database to retrieve relevant articles published in Indonesian. From the above exposures, it is explained that work accidents can be caused by human factors (unsafe action) and environmental factors (unsafe conditions). And it can be concluded that the application of PPE (Personal Protective Equipment) has a great effect on the number of accidents. Because Personal Protective Equipment (PPE) according to the Regulation of the Minister of Manpower and Transmigration in 2010 is a tool that has the ability to protect a person whose function is to isolate part or all of the body from potential dangers in the workplace. The use of PPE is the final stage of work accident control, its use will be important if there is a potential risk of work accidents. However, in reality, there are still many workers who do not use it even though they know the great benefits of using PPE.